2010
DOI: 10.1038/pcan.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in hormone-naïve prostate cancer patients treated with radical prostatectomy or definitive radiotherapy

Abstract: Chronic fatigue (CF) is a distressing symptom that follows cancer treatment; however, it has rarely been studied in hormone-naïve prostate cancer survivors after radical prostatectomy (RP) or definitive radiotherapy (RAD). We investigated CF in prostate cancer survivors after RP or RAD as monotherapy and explored associations between CF and medical and psychosocial variables. A population-based, cross-sectional postal survey in 2006 included Norwegian hormone-naïve survivors with the diagnosis of prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
3
14
0
1
Order By: Relevance
“…Chronic fatigue was defi ned as a sum score of ≥ 4 after dichotomization of the responses and duration for ≥ 6 months [ 14,15 ] .…”
Section: Questionnairementioning
confidence: 99%
“…Chronic fatigue was defi ned as a sum score of ≥ 4 after dichotomization of the responses and duration for ≥ 6 months [ 14,15 ] .…”
Section: Questionnairementioning
confidence: 99%
“…Norwegian studies have shown that 25-35 % of long-term survivors of breast cancer, lymphoma and cervical cancer are affected by chronic fatigue (4,(13)(14)(15), and that 26 % and 13 % of hormone-naïve men reported chronic fatigue two years after radical radiotherapy and radical prostatectomy for prostate cancer, respectively (16). Recently it was demonstrated that the prevalence of chronic fatigue in Norwegian testicular cancer survivors increased from 15 % twelve years after treatment to 27 % seven years later (17).…”
Section: Measurement and Prevalencementioning
confidence: 99%
“…Recently, however, a metaanalysis showed that the risk of severe fatigue among breast cancer survivors increased after combined treatment with surgery, chemotherapy and radiotherapy compared with surgery or surgery and radiotherapy alone (24). Radiotherapy has also been discussed as a possible aetiological factor for the development of chronic fatigue in prostate cancer survivors (16).…”
Section: Associated Factorsmentioning
confidence: 99%
See 2 more Smart Citations